2013
DOI: 10.1002/ejsp.1975
|View full text |Cite
|
Sign up to set email alerts
|

Warm or competent? Improving intergroup relations by addressing threatened identities of advantaged and disadvantaged groups

Abstract: Applying the Needs‐Based Model of Reconciliation to contexts of group disparity, two studies examined how messages from outgroup representatives that affirmed the warmth or competence of advantaged or disadvantaged groups influenced their members' intergroup attitudes. Study 1 involved natural groups differing in status; Study 2 experimentally manipulated status. In both studies, advantaged‐group members responded more favorably, reporting more positive outgroup attitudes and willingness to change the status q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…From perpetrators' more positive reactions (i.e., higher willingness to reconcile with the outgroup) to communion-reaffirming compared to agency-reaffirming messages it was concluded that they experienced a heightened need to restore their communal identity, whereas from victims' more positive reactions to agency-reaffirming (compared to communion-reaffirming) messages it was concluded that they experienced a heightened need to restore their agentic identity. The same approach was successfully used in contexts of structural inequality, referring to (Study 1) or manipulating (Study 2) the status of student participants' universities by pointing to unequal chances for admission to graduate programs (Shnabel, Ullrich, Nadler, Dovidio, & Aydin, 2013).…”
Section: Why Was This Study Done?mentioning
confidence: 99%
“…From perpetrators' more positive reactions (i.e., higher willingness to reconcile with the outgroup) to communion-reaffirming compared to agency-reaffirming messages it was concluded that they experienced a heightened need to restore their communal identity, whereas from victims' more positive reactions to agency-reaffirming (compared to communion-reaffirming) messages it was concluded that they experienced a heightened need to restore their agentic identity. The same approach was successfully used in contexts of structural inequality, referring to (Study 1) or manipulating (Study 2) the status of student participants' universities by pointing to unequal chances for admission to graduate programs (Shnabel, Ullrich, Nadler, Dovidio, & Aydin, 2013).…”
Section: Why Was This Study Done?mentioning
confidence: 99%
“…Whereas members of illegitimately advantaged groups experience threat to-and thus motivation to restore-their ingroup's communion (perceived warmth and prosociality), members of illegitimately disadvantaged groups experience threat to-and thus motivation to restore-their ingroup's agency (perceived power and capability) (Shnabel, Ullrich, Nadler, Dovidio, & Aydin, 2013;Siem, von Oettingen, Mummendey, & Nadler, 2013).…”
mentioning
confidence: 99%
“…Whereas disadvantaged group members experience threat to their status and identity as competent and are therefore motivated to gain respect (Bergsieker et al, 2010), advantaged group members experience threat to their moral identity (e.g., they may be perceived as prejudiced and bigoted, Fiske et al, 2002) and therefore seek moral-social acceptance (Bergsieker et al, 2010). Furthermore, whereas disadvantaged group members were found more willing to engage in collective action toward equality following an empowering, competence-reassuring message from their outgroup, advantaged group members were more willing to engage in social change action following an accepting message that reassured their moral identity (Shnabel et al, 2013). Further evidence that concerns about their moral identity play a critical role in determining advantaged group members' support of social movements comes from research findings that advantaged group members' support for different forms of collective action was primarily influenced by the extent to which these actions affect their ingroup's image as moral (which was even more important for them than the actual effectiveness of these actions in reducing inequality, Teixeira et al, 2019).…”
Section: Group Members' Needs For Empowerment and Morality: The Perspmentioning
confidence: 99%
“…From a theoretical perspective, the novelty of our research is that we integrate system justification and the different needs of advantaged and disadvantaged groups with support for a social change campaign in the context of gender relations. Previous research has highlighted the relevance of the needsbased model for supporting social change among advantaged and disadvantaged groups (see Shnabel et al, 2013), and the relevance of system justification and the needs-based model for understanding gender relations (see Hässler et al, 2019). However, no research has analyzed how the connection between system justification and support for social change is mediated by the different needs of advantaged and disadvantaged groups so far, and therefore, our findings can shed light on the ways in which social change can become acceptable for groups with different status in society.…”
Section: Research Question and Hypothesesmentioning
confidence: 99%